Excitons in coupled quantum dots: hydrostatic pressure and electric field effects (2009)
ABSTARCT: The variational procedure, in the effective-mass and parabolic-band approximations, is used in order to investigate the effects of hydrostatic pressure and in-growth direction applied electric field on the exciton states in vertically GaAs–Ga1–xAlx As coupled quantum dots. We have found that when the symmetrical lengths and radius of each QD are comparable with the Bohr radius of the GaAs material and for a finite value of the applied electric field, the binding energy always diminishes with the length of the central barrier because the two carriers in the exciton are localized in two well defined different regions of the system. However, for the zero electric field the binding energy decreases with the barrier width from the limit value corresponding to the exciton confined in one quantum dot of volume V up to reach a minimum and then increases to a value which corresponds to that of the exciton confined in an isolated quantum dot of volume V /2. Additionally, we have found that the applied electric field caninduce that the lowest structure in the photoluminescence-peak energy transitions be associated to spatially indirect excitons, situation which in the zero limit of the electric field and independent of the dimensions of the two coupled dots, always corresponds to spatially direct excitons. The main hydrostatic pressure effect reveals an increasing in the exciton binding energy, without modifying the direct or indirect exciton regime, and a well defined rigid blue-shift in the photoluminescence peak energy transitions in the presence of an applied electric field. (© 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)